Inner-Party Struggle in French Communist Party as Reflection of Internal Contradictions in Russian Communist Party (Bolsheviks) in 1920-ies - M. Y. Lugovtsova (Научный диалог, 2017)
The history of the formation of the French Communist party (FCP) in 1920-ies is considered. A review of the main historical events that had an important influence on the development of the Communist movement in Russia and in France is made. In particular, the importance of the internal party struggle in the Communist party of Russia and its impact on internal movement in the FCP is noted. The characteristic of the main political currents within the party is given. It is shown that the political confrontation between Stalin and Trotsky had a great influence on the future path of the Communists of France. It is emphasized that the main task of the heads of parties in the period under review was the creation of a unite Communist space with a single management structure and laws. Socio-political changes within both parties are analyzed. Also the opposition to the Communist movement in France and in Russia is discussed. The role of individual political figures in France and Russia influenced the development of the movement of Communists is analyzed.